Comparison of Anti-cyclic citrullinated peptide antiboby and Rheumatoid factor as a diagnostic marker in Rheumatiod arthritis (Bangladesh Journal of Medical Biochemistry, 2025)
Rheumatoid arthritis (RA) is a common chronic autoimmune disease affecting many systems, predominantly synovial joints. Early diagnosis and instillation of disease-modifying anti-rheumatic drugs treatment is mandatory to prevent its progression to joint destruction and permanent disability. To achieve an early diagnostic accuracy clinical application of American College of Rheumatology (ACR 1987) criteria along with (CRP) and (RF) have been practiced for a long period. Recently test for the antibodies directed to citrullinated peptides (anti-CCPA ) has been widely accepted as a biomarker for diagnosis of RA. This cross sectional study for the measurement of anti-CCPA and RF was conducted on 100 patients with chronic arthritis attending in rheumatology clinic in DMCH, Dhaka during the period July 2009 to August 2010. The specificity and sensitivity of anti-CCPA and RF were 90.24%, 100% and 73.17%, 77.78% respectively. Positive predictive value and negative predictive value of anti-CCPA and RF were 100%, 69.23% and 93.75%, 38.89%. The accuracy, positive likelihood ratio and negative likelihood ratio of anti- CCPA were 92%, 1 and 0.01. On the other hand these results of RF were 74%, 3.29 and 0.34. All the mentioned performance tests of this study support anti-CCPA to be a better diagnostic biomarker than RF in rheumatoid arthritis. Thereby measurement of anti-CCPA by itself is useful and widely accepted as indispensible tools for diagnosis of rheumatoid arthritis. However use of anti-CCPA and RF might be more strengthened than either method alone.Bangladesh J Med Biochem 2021; 14(1): 30-37